Multidimensional Poverty in the Perspective of Capability Approach: A Study of Informality and Gender Disparity in East Java - Hafizd, Achmad Haekal; Trapsila, Aji Putrba (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study examines the effects of informal employment and gender inequality on multidimensional poverty in East Java through the lens of the Capability Approach. Using 2024 National Socio-Economic Survey (Susenas) data covering 32,605 households (weighted to represent 11.2 million households), multidimensional poverty was measured with the Alkire-Foster method across eight indicators in education, health, and living standards. The findings reveal that 27.9% of households are multidimensionally poor, with an average deprivation intensity of 43.3% and an Adjusted Headcount Ratio (M0) of 0.121. Binary logistic regression shows that households with informal-sector heads are 2,1% more likely to fall into multidimensional poverty than those with formal-sector heads, while female-headed households face a 1.5% higher likelihood compared to male-headed households. These results indicate that multidimensional poverty in East Java is driven not only by demographic characteristics but also by structural labor market conditions and gender-based disparities. The study underscores the need for poverty alleviation strategies that address the vulnerabilities of informal workers and promote gender equality as integral components of inclusive development.